Effect of hunting awareness on wild game meat purchase behavior (International Journal of Health, Animal Science and Food Safety, 2018)
Although wild game meat constitutes a sustainable and healthy alternative to conventional meat and hunting contributes to the control of game populations, international studies on consumer attitudes towards this type of meat are still limited and no previous research has been focused on the Italian population.For the development of successful marketing strategies and/or public policy intervention, the knowledge of consumers’ purchase behavior is a key factor. Among all the determinants that can influence the behavior of consumers of hunted wild game meat (i.e. animal welfare, sustainability, ecological food choice, product safety, nutritional quality), the consumers’ awareness of hunting activity and their perceptions of wild game meat assume a crucial role.Accordingly, in this paper an online survey on a sample of 741 Italian meat consumers has been conducted to investigate the relationship between consumers’ purchase behavior and their awareness of hunted game meat and hunting practices (chi-square test, F-test). Statistically significant differences were found among segments of consumers with different levels of wild game meat consumption frequency. The analysis shows that, as expected, the highest consumption level of wild game meat relates to the highest level of general awareness of wild game meat and hunting practices.Our findings are in line with previous literature, that links positive behaviors of consumers towards wild game meat and hunting to familiarity and experience with hunting and hunters. Nonetheless, the present study provides a deeper understanding of the Italian consumers’ attitudes and perceptions of wild game meat and could suggests policy guidelines for the development of future targeted marketing strategies.
Keywords: Wild game meat; hunting; marketing strategies; consumer; survey